Research of Situational and Personality Determinants of Volitional Activity - Jo’raev O’tkir Tashpulatovich (Genius Publishing Group, 2023)
A criminal case has been opened on this fact, an investigation is underway. I.Selivanov understood will as an independent psychic process, a separate psychic sphere, like cognitive or emotional spheres.
Keywords: power; Will; activity; determinant